Implementasi Pembelajaran Matematika Berbasis Proyek untuk Mengembangkan Kemampuan Berpikir Kritis dan Kreatif Siswa Sekolah Dasar - Abdul Karim; Fatria Dalila; Deni Pratama (PGSD UNU NTB, 2025)
This study aims to analyze the implementation of project-based mathematics learning in developing critical and creative thinking skills of elementary school students. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group design. The subjects were fourth-grade students divided into two groups: the experimental class implementing Project-Based Learning and the control class with conventional learning. Data were collected through critical and creative thinking ability tests, observation of student activities, and documentation of project results. Data analysis used inferential statistical tests, N-Gain calculations, and descriptive analysis. The results showed a significant increase in critical and creative thinking skills of students in the experimental class compared to the control class. Students in the experimental class were better able to analyze problems, evaluate solutions, and generate diverse and original ideas. Learning activities also increased through active involvement in discussions, exploration, and project completion. Project products reflected a deeper understanding of concepts and high creativity. These findings indicate that project-based learning is effective in improving the quality of mathematics learning in elementary schools.